2004
DOI: 10.2151/jmsj.2004.761
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Seasonal Variation of Cloud over China Based on ISCCP Data and Surface Observations

Abstract: Based on the International Satellite Cloud Climatology Project (ISCCP) data, and the World Meteorological Organization (WMO) surface synoptic observations, spatial distributions and seasonal variations of total cloudiness and fractional cloud amount of high, middle and low clouds over China are examined. It is found that low clouds mainly appear along the southeast coast of China, middle clouds dominate southern China and high clouds mainly occur over northern China. Seasonal variations of convective clouds ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…The large positive MBE mainly located in southern China, in which the corresponding RMSE values are relatively large. This phenomenon can be easily explained, because southern China (20-35 • N, 103-120 • E) is the largest cloudy subtropical continental region in China (Yu et al, 2001), which was also confirmed by Li et al (2004) based on multi-year ISCCP data and surface cloud observations. If cloud distribution becomes more complicated, the accuracy of cloud parameters estimates (see Sect.…”
Section: Validation Of Hourly Ssr In the Haihe River Basinmentioning
confidence: 81%
“…The large positive MBE mainly located in southern China, in which the corresponding RMSE values are relatively large. This phenomenon can be easily explained, because southern China (20-35 • N, 103-120 • E) is the largest cloudy subtropical continental region in China (Yu et al, 2001), which was also confirmed by Li et al (2004) based on multi-year ISCCP data and surface cloud observations. If cloud distribution becomes more complicated, the accuracy of cloud parameters estimates (see Sect.…”
Section: Validation Of Hourly Ssr In the Haihe River Basinmentioning
confidence: 81%
“…There were some special features in different seasons. Unlike the other three seasons, summer has the highest frequency in the −10% to 0% range, which might due to the high occurrence frequency of cirrus in summer than in the other seasons since MODIS could detect more cirrus than the visual observation (Li et al 2004). Spring had higher frequency in the range of 60−100% (frequency: 4.35%) than the other seasons.…”
Section: Comparison Between Tccs and Tccmmentioning
confidence: 88%
“…The mid-to low-level divergence difference (or largescale rising motion that lies between) and the static stability are two primary large-scale dynamic and thermodynamic factors governing EC stratus clouds Li and Gu 2006;Zhang et al 2013). The dynamic component is examined by showing a vertical cross section for the cold-season mean divergence at each layer (Fig.…”
Section: A Simulated Dynamic and Thermodynamic Environmental Conditimentioning
confidence: 99%
“…The EC stratus clouds have strong relations with the orography-induced ambient environment Li and Gu 2006;Zhang et al 2013). They usually form under a stable stratification featured with moistening at the middle and low levels.…”
Section: Introductionmentioning
confidence: 99%